Conceptualizers in Japanese Kango - Švarcová, Zdenka (Acta Orientalia Vilnensia, 2005)
Charles University, Prague Looking at the Sino-Japanese (kango) part of the Japanese vocabulary we can see numerous examples of conceptualization within the frame of one niji kango that is a noun compound consisting of two characters (kanji). General notions like, for example, “consideration” (kō or kangae) or “thought” (sō or omoi) have been particularized by “attributes”, i. e. the preceding characters, suggesting the whole range of “considerations” (sank